Postpartum Depressive Symptoms: An Analysis of Social Determinants Using the Pregnancy Risk Assessment Monitoring System - Sarah O'Connor; Lihchyun Joseph Su (Mary Ann Liebert, 2023)
Background: Approximately one in every eight mothers experience symptoms of postpartum depression (PPD) in the United States.1 Existing literature lacks an in-depth exploration of the social context from which symptoms of PPD arise. The objectives of this study were to (1) determine the prevalence of postpartum depressive symptoms (PDS) among new mothers and to explore relationships between selected social determinants of health (SDOH) and the likelihood of experiencing PDS. Materials and Methods: Data were from the Pregnancy Risk Assessment Monitoring System (PRAMS) 2016 and 2017 Questionnaires. Measured SDOH included socioeconomic status, social network support, psychosocial stress, and availability of resources to meet basic daily needs. Outcome measurement included a combination of two symptom indicator questions. Univariate analyses yielded weighted frequencies of descriptive statistics according to PDS status, and bivariate and multivariate logistic regression analyses yielded odds of reporting PDS. Results: The prevalence of self-reported PDS was 3.5%. Among mothers with PDS, most (54%) lived at or below the federal poverty guideline. Mothers who experienced psychosocial stress (e.g., intimate partner violence) during pregnancy had the highest likelihood of reporting PDS (adjusted odds ratio [aOR]?=?3.60; confidence interval [95% CI], 2.12?6.12). Mothers who considered their most recent pregnancy unintended or mistimed were more likely to report PDS (aOR?=?1.36; 95% CI, 1.01?1.82), (aOR?=?1.65; 95% CI, 1.19?2.27), respectively. Conclusion: Results demonstrate that several social and psychosocial risk factors significantly impact the likelihood of experiencing PDS. The risk of PDS was particularly significant among lower socioeconomic status mothers, especially those with inadequate social network support. Public health efforts to mitigate potentially harmful social factors should focus on transforming public policies and social programs and increasing screening opportunities.